Paraklet duchem Nowego Przymierza (J 14, 15-17) - Witczyk, Henryk (The Biblical Annals, 2017)
The author poses a difficult problem: how to understand the words of the first promise of the Holy Spirit (J 14, 16-17), in the light of this commonly accepted truth about the revealing activity of the Holy Spirit. It is in this promise that Jesus stresses His very presence, and that not only among His disciples but in them („will be in you”). Seeking to solve this problem, the author analyzes the more proximate context (J 14, 11-14) and the condition under which the gift of the Spirit is given (J 14, 15), which immediately precedes the promise and is closely connected with it. Then he goes on to explain the text of the promise of „another Advocate” and the „Spirit of truth” which − according to the words of Jesus − „remains with you [the disciples]” (J 14, 16-17). At each stage of the studies he comes to a conclusion that the Spirit of truth, called „another Advocate,” and promised by Jesus, is to play an extremely important role in the area of the new covenant between God and His people. After Jesus has gone to the Father, the Spirit will be with His disciples for ever. Thanks to Him, the fellowship of Jesus’ disciples will, a fellowship of a new covenant, a site of Jesus’ new presence and His activity. „Another Advocate” will continuously take care about it and support it. Moreover, the Spirit who „is Truth” will be made present by Jesus, who is „one” with the Father. A fellowship internally united, by the power of the Spirit, who is forever „in” the disciples, will, with Jesus, participate in that perfect bond of the covenant, which is the love of the Father and the Son.